Meneropong Makna Penderitaan Manusia Menurut Konsep Teodise C.S. Lewis - Esther Gunawan (Veritas : Jurnal Teologi dan Pelayanan, 2017)
When faced with the phenomena of human suffering the default of the evangelical community is to examine human suffering through the lens of God’s sovereignty and providence which are inevitable forces faced by human beings. An attitude of fate, which arises as a direct response to God’s absolute sovereignty, actually leads to a concept of practical fatalism. The close relationship between natural law and human responsibility is ultimately neglected. It is hoped that a study of C. S. Lewis’ concept of theodicy can provide a new paradigm for the Indonesian evangelical community as it pertains to the problem of human suffering. This new paradigm proffers an active and positive estimation of the role of natural law as general revelation underlying the phenomena of suffering by positing the idea about the natural context of human life and the idea of fixed and uniform natural laws as a key to understanding the phenomena of human suffering.